Introduction to organic spectroscopy - Harwood, Laurence M.; Claridge, Timothy D. W. (Oxford ; New York : Oxford University Press, 1997)
Modern spectroscopic techniques are now fundamental to the success of organic chemistry and it is essential that students and practitioners of this discipline have a sound understanding of these techniques. This book describes the four major instrumental methods used routinely by organic chemists; ultra-violet/visible, infrared and nuclear magnetic resonance spectroscopy, and mass spectrometry.
It includes a concise introduction to the physical background of each, describing how molecules interact with electromagnetic radiation (UV, IR, and NMR), or how they fragment when excited sufficiently, and how this information may be applied to the determination of chemical structures. It includes simple descriptions of instrumentation and the emphasis throughout is on modern methodology, such as the Fourier-transform approach to data analysis. Each chapter concludes with a problem section.
This book will be useful to those new to modern organic spectroscopic analysis and as reference material in chemistry teaching laboratories.
1. Introductory theory -- 2. Ultraviolet-visible spectroscopy -- 3. Infrared spectroscopy -- 4. Nuclear magnetic resonance spectroscopy: the basics -- 5. Nuclear magnetic resonance spectroscopy: further topics -- 6. Mass spectrometry.
Includes bibliographical references and index.
Keywords: Organic compounds -- Spectra; Chemistry, Organic; Spectrum analysis